Impact of cotton storage methods on fiber quality (Eurasian Journal of Research, Development and Innovation, 2022)
Improvement of methods of storage of picked cotton and increase of quality of stored cotton. Paying attention to the storage of fiber in closed places in order to maintain it’s viability,as well as to ensure quality storage of fiber.